Testosterone and Cortisol Release among Spanish Soccer Fans Watching the 2010 World Cup Final - van der Meij, Leander; Almela, Mercedes; Hidalgo, Vanesa; Villada, Carolina; IJzerman, Hans; van Lange, Paul A. M.; Salvador, Alicia (PLOS ONE, 2012)
This field study investigated the release of testosterone and cortisol of a vicarious winning experience in Spanish fans watching the finals between Spain and the Netherlands in the 2010 FIFA World Cup Soccer. Spanish fans (n = 50) watched the match with friends or family in a public place or at home and also participated in a control condition. Consistent with hypotheses, results revealed that testosterone and cortisol levels were higher when watching the match than on a control day. However, neither testosterone nor cortisol levels increased after the victory of the Spanish team. Moreover, the increase in testosterone secretion was not related to participants' sex, age or soccer fandom, but the increase in total cortisol secretion during the match was higher among men than among women and among fans that were younger. Also, increases in cortisol secretion were greater to the degree that people were a stronger fan of soccer. Level of fandom further appeared to account for the sex effect, but not for the age effect. Generally, the testosterone data from this study are in line with the challenge hypothesis, as testosterone levels of watchers increased to prepare their organism to defend or enhance their social status. The cortisol data from this study are in line with social self-preservation theory, as higher cortisol secretion among young and greater soccer fans suggests that especially they perceived that a negative outcome of the match would threaten their own social esteem.